Effects of straw size in buried straw layers on water movement in adjacent soil layers - Mingze, Yao; Bo, Li; Tieliang, Wang; Xue, Feng (International Journal of Agricultural and Biological Engineering, 2016)
Deeply buried straw retention can improve the soil content of organic matter, its capacity for moisture preservation, the agroecological environment utilization efficiency of water resources, ensuring a stable crop yield; at the same time, the quantitative effects of deeply buried straw retention on soil moisture have a direct influence on the promotion and application of the technology. Using an infiltration and evaporation experiment of a one-dimensional soil column, the effects of straw size on the water content of the straw and the adjacent soil were evaluated when the straw was deeply buried in soil; the infiltration and evaporation features of different sized straw and its adjacent soil were analyzed; the hydraulic conductivity, sorptivity and saturated water content of the straw were obtained; in the end, the water distribution laws of straw and adjacent soil under the same conditions were concluded. The experiment was comprised of rod-shaped straw (RS), segment-shaped straw (SS) and filament-shaped straw (FS) to control treatment (CK). The results indicated that from the perspective of infiltration, the infiltration rate of filament-shape straw was the lowest at the stage of straw unsaturation. The hydraulic conductivities of rod-shaped, filament-shaped and segment-shaped straws are 4.01 mm/min, 1.33 mm/min and 0.03 mm/min at the stage of straw and adjacent soil saturation, respectively. There is a strong effect on preventing infiltration from segment-shaped straw; with the help of the Philip model of long duration, the sorptivity of the soil with rod-shaped, filament-shaped and segment-shaped straws was 12.31 mm/min0.5, 11.02 mm/min0.5 and 24.26 mm/min0.5 at the unsaturation stage, respectively. The segment-shape straw improved the water absorption capacity of the soil and straw column. The water retention capacities indicated that the saturated water contents of sandy loam, filament-shaped straw, segment-shaped straw and rod-shaped straw were 0.38 cm3/cm3, 0.29 cm3/cm3, 0.26 cm3/cm3 and 0.13 cm3/cm3, respectively. Additionally, the evaporation rate indicated that the soil moisture content of soil below different straw layers retained approximately 30%; that the more crushed the straw was, the more moisture the straw layer lost; and that the cumulative evaporation of rod-shaped straw, filament-shaped straw and segment-shaped straw within 120 days was 1.5 mm, 13.5 mm and 25.5 mm, respectively. Keywords: deeply buried straw, straw size, soil moisture, infiltration, evaporation, water retention DOI: 10.3965/j.ijabe.20160902.2068 Citation: Yao M Z, Li B, Wang T L, Feng X. Effects of straw size in buried straw layers on water movement in adjacent soil layers. Int J Agric & Biol Eng, 2016; 9(2): 74－84.